(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article illuminates the problems of studying of a scientific activity of Narynbek Ashyralievich Alymkulov (25.04.1958 – 11.01.2022), a gifted Kyrgyz historian, Candidate of Historical Sciences, Associate Professor of the Kyrgyz National University named after Jusup Balasagyn, the expert who researched the issues of the history of wars. He became one of the leading Kyrgyz specialists in the study of the history of World War II (1939–1945) and the role of Kyrgyz participants in the Great Patriotic War (1941–1945). By the end of April 2025, i.e. on the eve of the official celebration of the 80th anniversary of the Great Victory over German Nazism, the National Academy of Sciences of the Kyrgyz Republic published a book by the late scientist entitled “Heroes of the Soviet Union and Full Cavaliers of the Order of Glory – Kyrgyzstanis: New Facts, Names,” which is part of his main creative legacy. The article also examines issues related to the biography and other creative developments of the late historian Narynbek Alymkulov.